Preparation method and quality control method of white mulberry root-bark furosina decoction pieces
By moistening, drying and cutting the mulberry white bark medicinal materials, a high uniform mulberry white bark furuzu tablet was prepared, which solved the problem of poor quality uniformity of traditional decoctions and improved the quality and efficacy of decoctions.
Patent Information
- Application Number
- CN202510113344.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
AI Technical Summary
The thickness and width of existing traditional mulberry white bark tablets vary greatly between different origins, resulting in poor uniformity of the tablets and affecting the clinical application effect.
Use moisturized and drying mulberry white bark medicinal materials, cut into small pieces of 4-6mm specifications, and prepare them into furosour tablets. Through the optimization of the preparation process and quality control methods, ensure the quality uniformity of the tablets.
Through the optimization of preparation methods and quality control, the appearance characteristics, yield of mulberry fuzui tablets, the content of mulberry fuzui tablets, and the yield of mulberry oxidine tablets are improved, ensuring the uniformity of the quality and efficacy of the tablets.
Smart Images

Figure CN119792385A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of traditional Chinese medicine, and in particular to a preparation method and a quality control method of Morus alba bark decoction pieces. Background Art
[0002] Mulberry bark is the dried root bark of the mulberry plant (Morus alba L.) of the Moraceae family. It was first recorded in the "Shennong Bencao Jing" and has been included in the herbal medicines of all dynasties. It has appeared as the main drug in classic prescriptions many times. It is sweet and cold in nature, belongs to the lung meridian, has the effects of purging the lungs and relieving asthma, promoting diuresis and reducing swelling, and is often used clinically to treat lung heat, asthma, cough, edema and fullness. However, the thickness and width of traditional Morus alba bark slices vary greatly from different origins. When used for clinical adjustment, the quality uniformity of the slices is poor, which seriously affects its effect in clinical application. Many slices with larger and irregular shapes also have similar problems, which has attracted the attention of many scholars. The concept of new Chinese medicine slices has been proposed, including ultra-fine slices, broken wall slices, and formula granules. However, these new medicinal forms of slices have lost the apparent morphology of the slices, and it is difficult to evaluate the quality of the slices based on "distinguishing appearance from quality". Adhering to the concept of inheritance and innovation, the research team sorted out the historical evolution of the slices. The original form of the slices was " "Jiushe" or "Jiushe slices", after the Wei and Jin Dynasties, it was "smashed" into coarse powder, and in the Northern Song Dynasty, it was mostly coarse powder boiled and scattered. After the Ming Dynasty, it was "drinking slices". "Jiushe" retains the identification characteristics of traditional medicinal pieces, has the characteristics of high utilization rate, uniform quality, and easy dispensing, which can effectively save medicinal resources and ensure clinical efficacy; at the same time, with the high-quality development of hospital pharmaceutical services, the demand for standardized medicinal pieces for automated and intelligent dispensing in hospital pharmacies needs to be urgently addressed. The research on chewing decoction pieces has broad development prospects. In the critical period of inheritance and innovation of traditional Chinese medicine, it is necessary to realize the The modern development and utilization of chewed medicinal slices is also of great significance to the high-quality development of the traditional Chinese medicine industry. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method and quality control method of Morus alba bark decoction pieces to solve the problems existing in the above-mentioned prior art.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] The invention provides a method for preparing a Morus alba bark decoction piece. The preparation method comprises the following steps: steaming the Morus alba bark medicinal material for 20-30 minutes, cutting it into small pieces with a specification of 4-6 mm, and drying the pieces to obtain the Morus alba bark decoction piece.
[0006] Optionally, the method of moistening is: covering the Morus alba bark medicinal material with two layers of wet gauze and spraying water every 10 minutes.
[0007] Furthermore, the drying temperature is 60-70°C.
[0008] The present invention also provides Morus alba bark decoction pieces prepared by the above-mentioned preparation method.
[0009] The present invention also provides a method for preparing a standard decoction of Morus alba bark slices, comprising soaking the Morus alba bark slices in water, performing a first decoction and a second decoction, combining the two decoctions to obtain the standard decoction of Morus alba bark slices.
[0010] Furthermore, during the soaking, the mass ratio of the Morus alba bark decoction pieces to the water is 1:10-12; and the soaking time is 20-40 minutes.
[0011] Furthermore, the first decoction time is 15-30 minutes, and the second decoction time is 15-30 minutes.
[0012] The present invention also provides a quality control method for the above-mentioned Morus alba bark decoction pieces, comprising:
[0013] (1) performing powder microscopic identification on the Morus alba bark decoction pieces;
[0014] (2) Testing the moisture content, total ash content and extract of the Morus alba bark decoction pieces; the moisture content of the Morus alba bark decoction pieces shall not exceed 10.0%, the total ash content shall not exceed 7.5%, and the extract shall not be less than 16.0%;
[0015] (3) performing thin layer chromatography identification on the Morus alba bark decoction pieces;
[0016] (4) The content of mulberry glycoside A in the Morus alba bark decoction pieces is detected by high performance liquid chromatography; the content of mulberry glycoside A shall not be less than 2.0%.
[0017] Furthermore, the thin layer chromatography identification method is as follows: 3 μL of the test solution and the reference solution are taken, spotted on a silica gel G thin layer plate, using dichloromethane: ethyl acetate: methanol: acetic acid in a volume ratio of 1:6:2.5:0.1 as a developing solvent, pre-saturated for 20 minutes, developed, taken out, dried, and observed under a 365 nm ultraviolet lamp;
[0018] The preparation method of the test solution is as follows: the sample powder to be tested is mixed with ethanol in a ratio of 1 g: 30 mL, ultrasonically treated for 30 min under the conditions of 40 kHz and 250 W, filtered, and the filtrate is dried to obtain the test powder; the test powder is dissolved in ethanol in a ratio of 1 g: 5 mL to obtain the test solution;
[0019] The preparation method of the reference substance solution is as follows: taking the mulberry glycoside A reference substance, adding methanol to prepare a solution containing 0.3 mg per 1 mL, and obtaining the reference substance solution.
[0020] Furthermore, the method of high performance liquid chromatography detection is: 10 μL of the reference solution and the test solution are taken, injected into a liquid chromatograph, and chromatographed;
[0021] The chromatographic conditions are as follows: octadecylsilane bonded silica gel as filler, 0.05% phosphoric acid water as mobile phase A, acetonitrile as mobile phase B, gradient elution as shown in the table below; detection wavelength: 325 nm; column temperature: 35° C.; flow rate: 1.0 mL / min; injection volume: 10 μL;
[0022] The preparation method of the test solution is as follows: 0.5 g of the sample powder to be tested after passing through a No. 4 sieve is taken, 25 mL of 70% methanol is precisely added, ultrasonic treatment is performed for 45 min under the conditions of 40 kHz and 250 W, after constant volume, the sample is shaken, filtered, and constant volume is obtained to obtain the test solution;
[0023] The preparation method of the reference substance solution is as follows: taking the mulberry glycoside A reference substance and adding 70% methanol to prepare a solution containing 0.5 g per 1 mL, thereby obtaining the reference substance solution.
[0024] The present invention discloses the following technical effects:
[0025] Based on the traditional decoction pieces of Morus alba, the present invention optimizes the preparation method of Morus alba by using the entropy weight TOPSIS comprehensive evaluation method with the appearance, decoction piece yield, mulberry glycoside A content, paste yield and traditional decoction transfer rate as evaluation indicators. The cutting specifications of the decoction pieces were determined. On this basis, the orthogonal test was used to optimize the processing technology with the moistening time and drying temperature as the influencing factors. It provides a basis for the production, processing and market development of chewable tablets.
[0026] The present invention further constructs the Morus alba bark The quality control method of chewed decoction pieces was improved, the TLC identification method in the "Chinese Pharmacopoeia" was determined, the HPLC detection method of mulberry glycoside A was determined, and the applicability and accuracy of the TLC identification method and the HPLC detection method were verified. It was determined that the moisture content in the chewed decoction pieces of Morus alba should not exceed 10.0%, the total ash content should not exceed 7.5%, the extract should not be less than 16.0%, and the content of mulberry glycoside A should not be less than 2.0%. The quality standard of chewing decoction pieces is Morus alba It laid the foundation for the industrialized and industrialized production of chewing slices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Morus alba bark Optimization results of water addition amount and soaking time in the preparation of standard decoction of chewable slices;
[0028] Figure 2 Morus alba bark The test results of the extract yield and morusin A content of the standard decoction of Juyin tablets at different decoction times;
[0029] Figure 3 For traditional medicinal materials and Comparison results of the paste yield during the decoction process of chewing slices;
[0030] Figure 4 For traditional medicinal materials and Comparison results of the content of morusin A during the decoction process of the decoction pieces;
[0031] Figure 5 The microscopic identification characteristics of Morus alba bark decoction pieces powder of batch number F2308001 (A) and batch number F2308002 (B);
[0032] Figure 6 The microscopic identification characteristics of Morus alba bark furan slices powder of batch number F2308003 (A) and batch number F2308004 (B);
[0033] Figure 7 The microscopic identification characteristics of Morus alba bark decoction pieces powder of batch number F2308005 (A) and batch number F2308006 (B);
[0034] Figure 8 The microscopic identification characteristics of Morus alba bark decoction pieces powder of batch number F2308007 (A) and batch number F2308008 (B);
[0035] Fig. 9 The microscopic identification characteristics of Morus alba bark decoction pieces powder of batch number F2309009 (A) and batch number F2309010 (B);
[0036] Fig.10 The microscopic identification characteristics of Morus alba bark decoction pieces powder of batch number F2309011 (A) and batch number F2309012 (B);
[0037] Fig.11 The microscopic identification characteristics of Morus alba bark decoction pieces powder with batch number F2309013 (A), batch number F20230323-02 (B) and batch number F20230323-03 (C);
[0038] Fig.12It is a thin layer chromatogram of Morus alba bark medicinal material-original decoction piece-Fuju decoction piece; wherein, in A, 1 and 5 are both mulberry glycoside A reference substances, 2-4 are respectively Morus alba bark medicinal materials, pharmacopoeia decoction pieces, and Fuju decoction pieces of the same batch, 6-8 are respectively Morus alba bark medicinal materials, pharmacopoeia decoction pieces, and Fuju decoction pieces of the same batch; in B, 1 is mulberry glycoside A reference substance, 2-16 are respectively 15 batches of Morus alba bark Fuju decoction piece samples;
[0039] Fig.13 The thin layer chromatograms of Morus alba bark decoction pieces with different extraction solvents;
[0040] Fig.14 The thin layer chromatograms of Morus alba bark decoction pieces with different sample amounts;
[0041] Fig.15 The thin layer chromatograms of Morus alba bark furan slices made from thin layer plates of different manufacturers;
[0042] Fig.16 The thin layer chromatograms of Morus alba bark decoction pieces collected by different sampling personnel;
[0043] Fig.17 is the HPLC chromatogram of Mulberry glycoside A under time gradient 1;
[0044] Fig.18 is the HPLC chromatogram of Mulberry glycoside A under time gradient 2;
[0045] Fig.19 is the HPLC chromatogram of mulberry glycoside A at different flow rates;
[0046] Fig. 20 The HPLC chromatograms of Mulberry glycoside A at different column temperatures;
[0047] Fig.21 This is the HPLC chromatogram of Mulberry glycoside A in the Agilent chromatographic column;
[0048] Fig. 22 This is a high performance liquid chromatogram of mulberry glycoside A in a Welch Xtimate column;
[0049] Fig.23 This is the HPLC chromatogram of mulberry glycoside A in the Phenomenex Luna column;
[0050] Fig.24 It is the high performance liquid chromatogram of mulberry glycoside A at 325 nm;
[0051] Fig.25 This is the HPLC chromatogram of the Mulberry glycoside A reference substance;
[0052] Fig.26 This is the HPLC chromatogram of mulberry glycoside A in Fuju decoction pieces;
[0053] Fig. 27 It is the standard curve of the peak area of Mulberoside A reference substance in high performance liquid chromatography;
[0054] Fig.28 is the detection limit chromatogram of mulberry glycoside A in high performance liquid chromatography;
[0055] Fig.29 This is the chromatogram of the quantification limit of mulberry glycoside A in high performance liquid chromatography. DETAILED DESCRIPTION
[0056] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0057] Example 1 Optimization of the preparation method of Morus alba bark slices
[0058] 1. Materials
[0059] Morus alba L. medicinal materials (batch number 20230323-01, 20230323-02, 20230323-03; origin: Bozhou, Anhui) were provided by China Resources Sanjiu Pharmaceutical Group Co., Ltd. and identified as dried root bark of Morus alba L. by researchers from the Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences. Mulberry glycoside A (batch number: CHB231201, Chengdu Kroma Biotechnology Co., Ltd., purity ≥ 98.0%); methanol, ethanol, ethyl acetate, dichloromethane, and acetic acid were all analytical grade (Tianjin Damao Chemical Reagent Factory); water was Wahaha purified water (provided by Hangzhou Wahaha Group Co., Ltd.); acetonitrile and methanol were chromatographic grade (Shanghai Xingke High Purity Solvent Co., Ltd.).
[0060] 2. Experimental methods and results
[0061] 2.1 Optimization of the specifications of chewable slices
[0062] Take 800g of Morus alba bark (batch number: 230323-01), mix evenly, divide into 4 parts, remove impurities, wash with water, place Morus alba bark in a suitable container, cover with two layers of wet gauze, moisten for 30 minutes, cut into pieces of different sizes (4-6mm, 6-8mm, 8-10mm), dry at 60℃, and obtain Morus alba bark of different sizes. Different specifications of Morus alba slices were evaluated, and the specifications of slices recorded in the pharmacopoeia were used as the control. The content of mulberry glycoside A in the slices, the rate of extracting paste, the transfer rate of standard decoction, and the content of mulberry glycoside A in the decoction were used as indicators. The entropy weight TOPSIS method was used to optimize the selection of Morus alba slices. Specifications for chewing slices.
[0063] 2.1.1 Dry paste rate
[0064] Morus alba bark Chew about 20g of the decoction piece, add 12 times the amount of water, soak for 30 minutes, heat over high heat, and simmer for 30 minutes over low heat after the water boils. Filter while hot (100 mesh sieve), and cool the filtrate to room temperature; add 10 times the amount of water to the residue, continue to boil, and simmer for 20 minutes over low heat after the water boils. Filter while hot, cool the filtrate to room temperature, combine the two medicinal solutions, concentrate and fix the volume to 100mL, and mix well.
[0065] Accurately measure 10 mL of the above decoction and place it in an evaporating dish with a constant mass, concentrate it to dryness on a water bath, dry it in an oven at 105°C for 3 hours, cool it in a desiccator for 30 minutes, and quickly and accurately weigh it. Determine the solid content and calculate the paste yield of the traditional decoction.
[0066] 2.1.2 Transfer rate of mulberry glycoside A
[0067] The content of morusin A in the Morus alba slices and decoction was determined respectively, and the transfer rate was calculated according to the following formula:
[0068]
[0069] The determination process of mulberry glycoside A content is as follows:
[0070] Preparation of test solution: Take 0.5 g of the powder of Morus alba bark slices or the concentrated paste of decoction, accurately weigh, put it in a stoppered conical flask, accurately add 25 mL of 70% methanol, weigh the weight, ultrasonically treat (power 250 W, frequency 40 kHz) for 45 minutes, cool, weigh again, make up the lost weight with 70% methanol, shake well, filter, and remove the filtrate to obtain the test solution.
[0071] Preparation of reference solution: Take an appropriate amount of mulberry glycoside A reference substance, weigh it accurately, and add 70% methanol to make a solution containing 0.5 mg per 1 mL.
[0072] Chromatographic conditions and system suitability test: Octadecylsilane bonded silica gel was used as filler, the mobile phase was acetonitrile (A)-0.05% phosphoric acid water (B) gradient elution, and the time sequence of the elution gradient was: 0-5 min, 92%-91% A, 5-10 min, 91%-91% A, 10-15 min, 91%-90% A, 15-20 min, 90%-90% A. Detection wavelength: 325 nm; column temperature: 35°C; injection volume: 10 μL, flow rate 1.0 mL / min.
[0073] 2.1.3 Determination results of dry extract rate and mulberry glycoside A transfer rate
[0074] As shown in Table 1, there are differences in the content of Morus alba slices of different specifications, indicating that the cutting specifications have a certain influence on the quality of Morus alba slices. The statistical results show that there are significant differences among the three specifications. As the size of chewed pieces decreases, the paste yield of traditional decoctions increases, among which the paste yield of 6-8mm and 8-10mm pieces is lower than that of pharmacopoeia pieces, and 4-6mm is 18.62% higher than that of pharmacopoeia pieces. The transfer rate results of mulberry glycoside A show that the transfer rate of 4-6mm and 6-8mm pieces is higher than that of pharmacopoeia pieces, among which the content of mulberry glycoside A in 6-8mm piece is closer to that of pharmacopoeia pieces, and that of 4-6mm piece is 30.35% higher than that of pharmacopoeia pieces.
[0075] Table 1 Different specifications of Morus alba bark Test results of chewed decoction pieces and standard decoctions of pharmacopoeia specifications
[0076]
[0077] 2.1.4 Entropy Weight TOPSIS Evaluation
[0078] The entropy weight method is a method for determining weights based on the data itself. It is derived from the concept of information entropy and is used to measure the degree of discreteness of indicators. The weight of indicators is determined according to the amount of information in the data. The greater the difference in indicators, the greater the weight. TOPSIS is an approximate ideal ranking method, also known as the superior and inferior solution distance method. By calculating the Euclidean distance between the evaluation object and the optimal solution and the worst solution, the degree of closeness between the evaluation object and the ideal solution is obtained, and then the evaluation object is evaluated relatively.
[0079] according to The quality attributes of traditional decoctions (extraction rate, transfer rate) of chewed slices are not lower than those of pharmacopoeia-specified slices and are consistent with pharmacopoeia specifications. Taking cutting efficiency into consideration, as shown in Tables 2-4, Morus alba bark was selected. The cutting specifications of the chewing slices are 4-6mm blocks.
[0080] Table 2 Results of weight calculation using entropy method
[0081]
[0082] Table 3 TOPSIS evaluation calculation results
[0083]
[0084] Table 4 Positive and negative ideal solutions
[0085]
[0086]
[0087] 2.2 Optimization of the moistening time
[0088] Take 300g of mulberry bark medicinal material (batch: 20230323-03), divide it into 3 parts, weigh it accurately to remove impurities, rinse it with water, and soak it for different times. Cover it with two layers of wet gauze during soaking. Spray water if necessary, especially for relatively coarse medicinal materials, spray water once every 10 minutes. The mulberry bark medicinal material does not need to be completely soaked. It is slightly softened and has a slightly hard texture, which is easy to cut, and it is not easy to have a continuous knife phenomenon. The softening time was investigated with the content of mulberry glycoside A (determination method see 2.1.2) and the yield of the decoction piece as indicators. The soaking time of 20min, 30min, and 40min was selected as the factor level, and its content was compared. When the soaking time was 30min, the content of mulberry glycoside A was the highest. The results are shown in Table 5.
[0089] Table 5 Investigation on the moistening time of Morus alba bark
[0090]
[0091] 2.3 Optimization of drying temperature
[0092] Take 300g of Morus alba bark medicinal material (batch: 20230323-03), remove impurities, rinse with water, moisten for 30 minutes, cut into 4-6mm blocks, mix evenly, divide into 3 parts, place in ovens at 50℃, 60℃, and 70℃, spread 1-2cm thick, dry, take out, and cool. The drying temperature was investigated with properties, moisture, and mulberry glycoside A content (determination method see 2.1.2) as indicators. The results are shown in Table 6. Under the condition of a certain moistening time, as the drying temperature increases, the mulberry glycoside A content decreases with the increase of temperature. Excessive temperature will cause the active ingredients to be destroyed and the content of the active ingredients to decrease. On the whole, the time required for drying at 60℃ is not long and the content is high, so the optimal drying temperature is determined to be 60℃.
[0093] Table 6 Morus alba bark Investigation on drying temperature of chewing tablets
[0094]
[0095] 2.4 Orthogonal experiment
[0096] The steaming time and drying temperature were used as the investigation factors. Through single factor experiments, the levels of each factor were determined. The properties of chewed pieces and the content of morusin A were used as evaluation indicators for the evaluation of Morus alba The processing technology of chewing decoction pieces was optimized, and the factor levels are shown in Table 7. The medicinal material of Morus alba was divided into 9 portions, each with 100g, and Morus alba was processed according to the orthogonal experimental design scheme. The chewed pieces are in the form of pieces, with a white or light yellowish white outer surface, relatively flat, and some with residual orange-yellow or brownish yellow scaly rough skin; the inner surface is yellowish white or grayish yellow with fine vertical lines. The best process was selected. The results are shown in Tables 8 and 9. From the intuitive analysis, it can be seen that the order of influence of various factors on the processing technology is B>A. Therefore, the preparation of Morus alba bark medicinal materials The best process for chewing the slices is to steam for 30 minutes and dry at 60℃.
[0097] Table 7 Morus alba bark Orthogonal test factor level of L9(34) preparation process of chewing slices
[0098]
[0099]
[0100] Table 8 Morus alba bark Results of orthogonal test on preparation technology of chewing slices L9(34)
[0101]
[0102] Table 9 Analysis of variance
[0103]
[0104] 2.5 Small-scale process verification
[0105] According to the selected Morus alba Preparation process of chewing slices: Take 3 batches of Morus alba bark medicinal materials (20230323-1, 20230323-2, 20230323-3), about 100g of each batch, remove impurities, wash with water, soak for 30 minutes, cut into 4-6mm pieces, dry in a 60℃ oven, take out, and cool. Prepare 3 batches of Morus alba bark according to the best conditions The slices were chewed and three validation tests were carried out. The experimental results are shown in Table 10. The three batches of Morus alba bark prepared by the pilot process were validated. The yield, moisture content and mulberry glycoside A content of the chewed pieces all meet the requirements. The relative standard deviation (RSD) of the content of different test points in the same batch of chewing slices was small, and the content change rate during the processing process was basically consistent, indicating that the process was stable and feasible. The preparation process of chewing slices has certain stability and reliability, and has reference value and operability.
[0106] Table 10 Morus alba bark Small-scale test results of chewing herbal medicine slices
[0107]
[0108]
[0109] 3. Optimization of the preparation method of standard decoction of chewed slices
[0110] 3.1 Optimization of water addition ratio for decoction
[0111] Weigh 3 portions of Morus alba bark About 20g of the slices (batch number: 230323-04) were chewed, and water of different weight multiples (8 times, 10 times, 12 times) was added to the slices, and the soaking liquid was filtered through a 0.22 microporous membrane, and the content of mulberry glycoside A was detected in the liquid phase. Figure 1 , indicating that the content of mulberry glycoside A is highest when 12 times the amount of water is added.
[0112] 3.2 Optimization of decoction and soaking time
[0113] Weigh 5 portions of Morus alba bark About 20g of the chewable tablets (batch number: 230323-04) were added with 12 times the amount of water and soaked for different time periods (0, 10, 20, 30, 40min). The soaking liquid was filtered through a 0.22 microporous membrane and the content of mulberry glycoside A was detected in the liquid phase. The results are shown in Figure 1 , indicating that the content of mulberry glycoside A was the highest when soaked for 30 minutes.
[0114] 3.3 Optimization of decoction time
[0115] Morus alba bark About 20g of the chewable slices (batch number: 230323-04), a total of 12 portions, add 12 times the amount of water, soak for 30 minutes, and decoct. Take 0min (after soaking for 30 minutes), 5min, 10min, 15min, 20min of the first decoction and 5min, 10min, 15min, 20min of the second decoction as the time points for investigation during the decoction process. The first decoction is to add 12 times the amount of water, boil and then change to a low heat, at the corresponding time point, filter through a 100-mesh sieve, and adjust the filtrate to 210mL (because the filtered medicinal liquid after soaking for 30 minutes is 210mL), the second decoction is to add 10 times the amount of water, and the other steps are consistent with the first decoction. Take 10mL of the medicinal liquid obtained at different time points to make a paste rate inspection and mulberry glycoside A content inspection. The results are shown in Figure 2 , when decocted, mulberry bark When the slices are chewed for 30 minutes, the content of mulberry glycoside A is relatively high. The content of mulberry glycoside A was higher when the slices were decocted at 20 minutes. The content of mulberry glycoside A and the rate of extracting paste decreased after the first 30 minutes and the second 20 minutes. The first and second decoction times of the decoction pieces are 30 and 20 minutes respectively.
[0116] 4. Traditional herbal medicines and Quality evaluation of chewing slices
[0117] The purpose of the present invention is to improve the uniformity of the Morus alba slices, increase their utilization rate, and make clinical adjustment more convenient. The quality of chewing pieces was compared, with texture, color, size uniformity, mulberry glycoside A content, decoction yield and mulberry glycoside A content as indicators for comparison, and the quality of traditional pieces and chewing pieces was investigated. The transfer rate of the main component of Morus alba A when chewing the slices is to ensure the The content uniformity and efficacy of chewable tablets. The results are shown in Table 11. Figure 3 , 4 For traditional medicine and The comparison chart of the yield of paste and the content of mulberry glycoside A during the decoction of the decoction pieces shows the yield of paste. The decoction of chewed slices was superior to that of traditional slices; there was no significant difference in the content of mulberry glycoside A, and the difference was within 0.3%, indicating that There is no significant difference between chewed medicinal slices and traditional medicinal slices in preparing standard decoctions.
[0118] Table 11 Comparison results of Morus alba bark medicinal materials and decoction pieces
[0119]
[0120]
[0121] Embodiment 2 Determination of the quality control method of Morus alba bark decoction pieces
[0122] 1. Sample source
[0123] Morus alba bark medicinal materials: from Qiaocheng District, Bozhou City, Anhui Province, batches are F2308001-F2308008, F2309009-F2309013, F20230323-02, F20230323-03;
[0124] Pharmacopoeia decoction pieces: Morus alba bark medicinal materials are prepared according to the records of the pharmacopoeia;
[0125] Fuzhu decoction pieces: 15 batches of Morus alba bark Fuzhu decoction pieces were prepared according to the optimized preparation method of Example 1: Take Morus alba bark medicinal material, remove impurities, separate into coarse and fine pieces, wash with water, soak for 30 minutes, cut into 4-6 mm pieces, place in a 60°C oven to dry until the moisture content is ≤10.0%, take out, cool, and sieve out the debris to obtain the product.
[0126] 2. Microscopic identification
[0127] Refer to the method under [Identification] of the 2020 edition of the Chinese Pharmacopoeia for identification. The microscopic identification characteristics of 15 batches of Morus alba furan slices powder are shown in Figure 5-Figure 19 .
[0128] 3. Thin layer identification
[0129] Because the thin layer identification method under the mulberry bark (2020 edition, Part I) has poor spot separation using polyamide film, and the sample preparation method has many steps, a new thin layer identification method is established. The specific process is as follows:
[0130] 3.1 Reagents
[0131] Reference substance: Mulberry glycoside A (batch number: CHB231201, purchased from Chengdu Kloma Biotechnology Co., Ltd.).
[0132] Other reagents: dichloromethane, methanol, ethyl acetate, and acetic acid were all of analytical grade; water was Wahaha purified water.
[0133] 3.2 Methods and Results
[0134] 3.2.1 Preparation of test solution: Take about 0.2 g of sample powder, add 6 mL of ethanol, ultrasonically treat (frequency 40 kHz, power 250 W) for 30 min, filter, evaporate the filtrate to dryness, take 1 mL of ethanol (≥99.7%) to dissolve, and use it as the test solution.
[0135] 3.2.2 Preparation of reference solution: Take an appropriate amount of mulberry glycoside A reference substance and add methanol (≥99.7%) to make a solution containing 0.3 mg per 1 mL as the reference solution.
[0136] 3.2.3 Determination method: According to the thin layer chromatography method (General Rule 0502), 3 μL of the test solution and the reference solution were taken and spotted on the same silica gel G thin layer plate, respectively. Dichloromethane: ethyl acetate: methanol: acetic acid (1:6:2.5:0.1) was used as the developing agent. After pre-saturation for 20 minutes, it was developed, taken out and dried. The determination process was carried out at 20°C and 45% humidity. It was examined under ultraviolet light (365nm). The results are as follows: Fig.12 shown. Fig.12 In A, 1 and 5 are both mulberry glycoside A reference substances, 2-4 are respectively mulberry bark medicinal materials, pharmacopoeia decoction pieces, and Fuju decoction pieces from the same batch, and 6-8 are respectively mulberry bark medicinal materials, pharmacopoeia decoction pieces, and Fuju decoction pieces from the same batch. Fig.12 In B, 1 is the mulberry glycoside A reference substance, and 2-16 are 15 batches of Morus alba bark furan decoction pieces samples. It can be seen that in the chromatogram of the test sample, the same main fluorescent spot is shown at the corresponding position of the chromatogram of the reference substance.
[0137] 3.3 Investigation of different extraction solvents
[0138] The 20230323-02 batch of Morus alba bark slices were selected and extracted with ethanol, methanol and ethyl acetate respectively according to the method of 3.2.1 to prepare the test solution. The plate was spotted with 3 μL of sample volume and developed according to the method of 3.2.3. The results are as follows Fig.13 As shown, 1 is mulberry glycoside A; 2 is ethanol (≥99.7%) extraction; 3 is methanol (≥99.7%) extraction; 4 is ethyl acetate extraction. It can be seen that when the extraction solvent is ethyl acetate, mulberry glycoside A is not displayed at all, and when the extraction solvent is methanol, the development spot is consistent with ethanol, and methanol has an obvious tailing phenomenon, so ethanol is selected as the extraction solvent.
[0139] 3.4 Investigation of different sampling quantities
[0140] Select the 20230323-02 batch of Morus alba bark decoction pieces, prepare the solution according to 3.2.1 and 3.2.2, spot the plate with 1, 3, 5, and 10 μL of sample volume, respectively, and develop according to 3.2.3. The results are as follows Fig.14 As shown, it can be seen that when the spotting volume is 1 μL, the mulberry glycoside A spot is lighter; when the spotting volume is 5 μL, the mulberry glycoside A spot is larger, and the spots on the upper end are accumulated; when the spotting volume is 3 μL, the spot is clear, and the other spots are clearly separated. Therefore, the spotting volume is selected to be 3 μL.
[0141] 3.5 Inspection of thin-layer boards from different manufacturers
[0142] The samples of Morus alba bark decoction pieces from batch 20230323-02 were selected, and the solution was prepared according to methods 3.2.1 and 3.2.2. The sample volume was 3 μL. The samples were developed according to method 3.2.3 and were developed on silica gel G thin layer plates from different manufacturers. The results are as follows: Fig.15 As shown, when other conditions are the same, the Shandong Qingdao thin layer plate has tailing and cannot be fully developed, the Shandong Yantai thin layer plate has mulberry glycoside A that is not developed, and the German Merck thin layer plate develops better. Therefore, the German Merck thin layer plate can be selected.
[0143] 3.6 Inspection of different sample personnel
[0144] Select the 20230323-02 batch of Morus alba bark Fuju decoction pieces, prepare the solution according to 3.2.1 and 3.2.2, spot the plate with a sample volume of 3 μL, and develop it according to 3.2.3. Two people in the laboratory spot the plate respectively. The results are as follows Fig.16 As shown, it can be seen that when other conditions are the same, the thin layer plates of mulberry glycoside A spotted by A and B tend to be consistent, indicating that this method is stable and applicable.
[0145] 4. Moisture detection
[0146] Refer to the second method of 0832 of the fourth general rules of the 2020 edition of the Chinese Pharmacopoeia for detection. Take 2-5g of the test sample, spread it flat in a flat weighing bottle dried to constant weight, with a thickness not exceeding 5mm, and the loose test sample should not exceed 10mm. Weigh it accurately, open the bottle cap and dry it at 100-105℃ for 5 hours, cover the bottle cap, move it to the dryer, let it cool for 30 minutes, weigh it accurately, and then dry it at the above temperature for 1 hour, let it cool, and weigh it again until the difference between two consecutive weighings does not exceed 5mg. Calculate the water content (%) in the test sample based on the lost weight. The results are shown in Table 12. It can be seen that the moisture content of 15 batches of Morus alba Fuju decoction pieces ranges from 5.03% to 8.11%, with an average of 6.80%. The moisture content under the Morus alba decoction piece item of the 2020 edition of the Chinese Pharmacopoeia shall not exceed 10.0%. According to the test results of moisture content of 15 batches of Morus alba bark slices, all of them meet the requirements. Therefore, it is temporarily stipulated that the moisture content of this product shall not exceed 10.0%, which is consistent with the current edition of the Pharmacopoeia.
[0147] Table 1215 batches of mulberry bark furan slices moisture determination results
[0148]
[0149] 5. Total ash detection
[0150] Refer to the general rules 2302 of the fourth part of the 2020 edition of the Chinese Pharmacopoeia for testing. Take 2-3g of the test sample, place it in a crucible that has been incinerated to constant weight, weigh it, slowly heat it, be careful to avoid burning, and when it is completely carbonized, gradually increase the temperature to 500-600℃ to completely ash it and reach constant weight. According to the weight of the residue, calculate the total ash content (%) in the test sample. The measurement results are shown in Table 13. It can be seen that the actual measured range of total ash content of 15 batches of mulberry bark furan slices is 4.82%-7.18%, with an average of 5.84%. There is no clear provision for total ash under the mulberry bark slices in the 2020 edition of the Chinese Pharmacopoeia. According to the experimental measurement results of the total ash content of 15 batches of mulberry bark furan slices, combined with the average of 5.84% of 130% is 7.59%, it is temporarily stipulated that the total ash content of this product shall not exceed 7.5%, and the total ash content of 15 batches of mulberry bark furan slices meets the requirements.
[0151] Table 1315 batches of total ash content test results of Morus alba bark Fuju decoction pieces
[0152]
[0153]
[0154] 6. Extractables detection
[0155] According to the hot soaking method under the 2020 edition of the "Chinese Pharmacopoeia" alcohol-soluble extract determination method (General Rule 2201), the contents of extracts from the cold soaking method and hot soaking method of Morus alba bark and different extraction solvents (10% ethanol, 30% ethanol, 50% ethanol, 70% ethanol, 90% ethanol) were investigated. The specific process is as follows:
[0156] 6.1 Cold and hot soaking tests using water and 50% ethanol as solvents
[0157] 6.1.1 Cold leaching method: Take about 2g of sample powder, weigh it accurately, put it in a 100mL conical flask, add 50mL of water or 50% ethanol accurately, plug it tightly, and soak it in cold water. Shake it from time to time within the first 6 hours, and then let it stand for 18 hours. Filter it quickly with a drying filter, accurately measure 25mL of the filtrate, put it in an evaporating dish that has been dried to constant weight, evaporate it on a water bath, dry it at 105℃ for 3 hours, cool it in a desiccator for 30 minutes, and quickly weigh it accurately. Perform two parallel experiments and calculate the content (%) of the extract in the test sample based on the dried product.
[0158] 6.1.2 Hot leaching method: Take about 2g of sample powder, weigh accurately, place in a 100mL conical flask, add 50mL of water or 50% ethanol accurately, seal, weigh, let stand for 1 hour, connect a reflux condenser, heat to boiling, and keep it slightly boiling for 1 hour. After cooling, remove the conical flask, seal, weigh again, make up the lost weight with solvent, shake well, filter with a drying filter, accurately measure 25mL of filtrate, place in an evaporating dish that has been dried to constant weight, evaporate to dryness on a water bath, dry at 105℃ for 3 hours, cool in a desiccator for 30 minutes, and quickly weigh accurately. Perform two parallel experiments and calculate the content (%) of the extract in the test sample based on the dried product.
[0159] The results are shown in Table 14. It can be seen that the hot leaching method has a high extract yield. There are large differences in filtration speed in different extraction solvents and different extraction methods, which has a great impact on the repeatability of the experimental results. When water is used as the solvent, suction filtration is used for hot and cold leaching filtration, which takes a long time, is difficult to operate, and has poor parallelism. When 50% ethanol is used as the solvent, the operation feasibility is better and can be filtered with filter paper.
[0160] Table 14 Results of the method investigation of extracts of Morus alba bark Fuju decoction pieces
[0161]
[0162] 6.2 Using hot leaching as the extraction method, investigating different concentrations of ethanol as the solvent
[0163] The extracts of Morus alba bark furan slices under different concentrations of ethanol (10%, 30%, 50%, 70%, 90%) were investigated by hot soaking method. The results are shown in Tables 15 and 16. The extracts of different concentrations of ethanol were subjected to one-way analysis of variance, and the results of Levene's variance homogeneity test showed that P=0.25, and the variance was homogeneous. There was no significant difference between 30% and 50% ethanol as solvents; there were significant differences between 10% and 30%, 50%, 70%, and 90%. The extract of 10% ethanol was higher, but it required suction filtration during filtration, and it took a long time, and the operational feasibility was poor. When filtering 30% and 50% ethanol, 50% ethanol was faster and had a lower time cost, so 50% ethanol could be selected as the extraction solvent.
[0164] Table 15 Results of different concentrations of ethanol extracts
[0165]
[0166] Table 16 One-way ANOVA of extracts from different concentrations of ethanol
[0167]
[0168] 6. Determination of extracts from 315 batches of Morus alba bark slices
[0169] The content of extracts from 15 batches of Morus alba bark furan slices was determined by hot immersion method, and 50% ethanol was used as the extraction solvent. The results are shown in Table 17. The measured results of extracts from 15 batches of Morus alba bark furan slices ranged from 16.71% to 22.03%, with an average of 20.00%. The 2020 edition of the Chinese Pharmacopoeia does not specify extracts under the Morus alba slices. According to the experimental determination results of extracts from 15 batches of Morus alba bark furan slices, combined with 80% of the average of 20.0%, it is 16.0%, so it is temporarily stipulated that the extract of this product shall not be less than 16.0%.
[0170] Table 1715 batches of extracts from Morus alba bark slices
[0171]
[0172] 7. Detection of mulberry glycoside A content
[0173] Mulberry glycoside A, as an important active ingredient in Morus alba bark, has pharmacological effects such as antitussive and antiasthmatic, tyrosinase inhibition and anti-oxidation, which are consistent with the main effects of Morus alba bark. After the Morus alba bark is decocted into a decoction, only the water-soluble component Mulberry glycoside A can be stably transferred to the decoction of Morus alba bark. Other active ingredients in Morus alba bark, such as flavonoid components morusin, mulberry flavonoid G, and coumarin component scopoletin, are difficult to be effectively transferred to the decoction due to their low solubility or interaction with other components. Therefore, Mulberry glycoside A was selected as the quantitative indicator of Morus alba bark decoction pieces.
[0174] The test solution was prepared by referring to the high performance liquid chromatography method (General Rule 0512). The test solution was prepared by taking 0.5 g of Morus alba bark decoction piece powder, accurately weighing it, accurately adding 25 mL of 70% methanol, ultrasonically treating it for 45 min, cooling it, making up for the weight loss, filtering it, and filtering it through a 0.22 μm microporous membrane to obtain the solution.
[0175] 7.1 Determination of chromatographic conditions
[0176] 7.1.1 Determination of mobile phase composition
[0177] The 20230323-02 batch of Morus alba furan slices samples were selected and injected with different mobile phases of 0.05% phosphoric acid-acetonitrile, 0.05% acetic acid-acetonitrile, and 0.05% formic acid-acetonitrile, and the results are shown in Table 18. From the peak area of mulberry glycoside A, there is no obvious difference in the three mobile phase ratios, but 0.05% phosphoric acid-acetonitrile has a slight preference for the separation of mulberry glycoside A from the sample, and the RAD value of 0.05% phosphoric acid-acetonitrile is the smallest. Therefore, 0.05% phosphoric acid-acetonitrile is selected as the mobile phase component of the content determination method of Morus alba furan slices.
[0178] Table 18 Peak area of mulberry glycoside A in different mobile phase samples
[0179]
[0180]
[0181] 7.1.2 Selection of mobile phase gradient
[0182] In terms of mobile phase gradient selection, isocratic elution and gradient elution were investigated respectively. The results are shown in Tables 19-21 and Figure 17-Figure 18 It can be seen that during isocratic elution, the peak of mulberry glycoside A appears earlier, is easily confused with the solvent peak, and has a smaller peak area. Therefore, gradient elution was selected.
[0183] Table 19 Time gradient 1
[0184]
[0185] Table 20 Time gradient 2
[0186]
[0187] Table 21 Peak area of mulberry glycoside A in different gradient samples
[0188]
[0189] 7.1.3 Investigation of different flow rates and column temperatures
[0190] The 20230323-02 batch of Morus alba (origin Anhui Bozhou) Fujue decoction pieces were selected to investigate the peak area of mulberry glycoside A under three column temperatures (30, 35, 40°C) and three flow rates (0.8, 1.0, 1.2 mL / min). The results are shown in Tables 22-23 and Figure 19-20 It can be seen that the peak area RSD of mulberry glycoside A at different column temperatures is between 0.32% and 1.00%, and the separation degree with adjacent peaks at 35°C column temperature fluctuates less and is more stable. Therefore, 35°C is selected for separation; the RSD of the peak area of mulberry glycoside A at different flow rates is between 0.08% and 0.97%, which is less than 2%, and the difference in separation degree with adjacent peaks is small, indicating that the flow rate has little effect on it, and the method has good durability.
[0191] Table 22 Peak area of mulberry glycoside A in samples investigated at different flow rates
[0192]
[0193] Table 23 Peak area of mulberry glycoside A in samples investigated at different temperatures
[0194]
[0195]
[0196] 7.1.4 Investigation of different chromatographic columns
[0197] The samples of Morus alba bark furan slices from batch 20230323-02 were selected to investigate the effects of Agilent TC-C18(2) column (4.6×250mm, 5μm), Welch Xtimate C18 column (4.6×250mm, 5μm) and Phenomenex LunaC18(2) column (4.6×250mm, 5μm) on mulberry glycoside A in Morus alba bark furan slices. Each group was replicated twice. The results are shown in Table 1. Figure 21-23 And Table 24. It can be seen that the separation degree of mulberry glycoside A under each chromatographic column is good, the retention time difference is small, and the RAD values of the peak area of mulberry glycoside A of each chromatographic column are 0.74%, 0.09% and 0.07%, respectively, indicating that different chromatographic columns have no effect on it, and the method has good durability.
[0198] Table 24 Peak area of mulberry glycoside A in samples from different chromatographic columns
[0199]
[0200] 7.1.5 Wavelength selection
[0201] According to the mobile phase determined above, the reference solution was injected and measured, and the reference solution was fully scanned in the wavelength range of 200-800nm. The results are shown in Fig.24 It can be seen that mulberry glycoside A has maximum absorption at wavelengths of 216 and 325 nm. The peak area at 325 nm is the largest and has good separation from adjacent chromatographic peaks. Taking into account terminal absorption, detection sensitivity and other interference factors, it was finally determined to detect mulberry glycoside A at a wavelength of 325 nm.
[0202] 7.1.6 Determination of chromatographic conditions
[0203] Chromatographic conditions and system suitability test: octadecylsilane bonded silica gel was used as filler, 0.05% phosphoric acid water was used as mobile phase A and acetonitrile was used as mobile phase B, and gradient elution was performed according to the records in Table 20; the detection wavelength was 325 nm. The theoretical plate number calculated based on the mulberry glycoside A peak should not be less than 8000. Column temperature: 35°C; flow rate: 1.0 mL / min.
[0204] 7.2 Investigation of test sample processing methods
[0205] 7.2.1 Investigation of different sieve sizes
[0206] The mulberry bark was passed through No. 2, No. 3 and No. 4 sieves respectively, and 0.5g, 1.0g and 2.0g of the mulberry bark powder (passed through No. 4 sieve) were taken, accurately weighed, accurately added with 25mL of 70% methanol, ultrasonically treated for 45min, cooled, supplemented with the weight loss, filtered, passed through a 0.22μm microporous filter membrane, and prepared into a test solution for detection. The results are shown in Table 25. The content determination results of the mulberry bark powder after passing through No. 4 sieve were relatively stable, and the peak area of mulberry glycoside A was relatively high.
[0207] Table 25 Peak area of mulberry glycoside A in samples with different sieve numbers
[0208]
[0209] 7.2.2 Investigation of material-liquid ratio
[0210] Take 0.5g, 1.0g, and 2.0g of the powder of Morus alba bark (passed through a No. 4 sieve), accurately weigh, accurately add 25mL of 70% methanol, ultrasonically treat for 45min, cool, make up for the weight loss, filter, and pass through a 0.22μm microporous filter membrane to obtain the result. The results are shown in Table 26. The chromatographic peak area of Mulberry glycoside A with a solid-liquid ratio of 1:50 is relatively large, among which the peak area with a sample weight of 0.5g is the largest. Considering comprehensively, the solid-liquid ratio of 1:50 and the sample weight of 0.5g are selected.
[0211] Table 26 Investigation of peak area of mulberry glycoside A at different material-liquid ratios (n=3)
[0212]
[0213] 7.2.3 Investigation of extraction solvent
[0214] Take 0.5g of the powder of Morus alba bark (pass through No. 4 sieve), weigh accurately, add 25mL of water, methanol and ethanol solvents respectively, ultrasonicate for 30min, cool, make up for weight loss, filter, and pass through a 0.22μm microporous filter membrane to obtain. The results are shown in Table 27. The peak area and overall response value of the chromatographic peak of Mulberry glycoside A extracted with methanol as solvent are greater than those of water and ethanol, and methanol has the characteristics of low viscosity and better solubility than ethanol, so methanol is selected as the extraction solvent. Then, 10%, 30%, 50%, 70%, and 100% methanol are used as extraction solvents to determine the peak area of the chromatographic peak of Mulberry glycoside A in the sample, and the results are shown in Table 28. The peak area of the chromatographic peak of Mulberry glycoside A extracted with 70% methanol is greater than that of other volume fractions of methanol, and finally 70% methanol is selected as the extraction solvent.
[0215] Table 27 Peak area of mulberry glycoside A in different solvents (n=2)
[0216]
[0217] Table 28 Peak area of mulberry glycoside A in different concentrations of methanol
[0218]
[0219]
[0220] 7.2.4 Investigation of extraction methods
[0221] Take 0.5g of the powder of Morus alba bark (pass through No. 4 sieve), accurately weigh, add 25mL of 70% methanol, ultrasonic (15, 30, 45, 60min) and reflux (30, 60, 90min), cool, make up for weight loss, filter, pass through 0.22μm microporous filter membrane, and obtain. The results are shown in Table 29 and Table 30. The peak area of the chromatographic peak of Mulberry glycoside A by ultrasonic (15, 30, 45, 60min) and reflux (30, 60, 90min) is compared. The results show that the peak area of the target peak by different extraction methods is not much different, among which the peak area of ultrasonic 45min is the highest; the RSD value is relatively small. Considering comprehensively, the selected extraction method is ultrasonic 45min.
[0222] Table 29 Investigation of peak area of mulberry glycoside A at different ultrasound times (n=3)
[0223]
[0224] Table 30 Investigation of the peak area of Mulberry glycoside A at different reflux times (n=3)
[0225]
[0226] 7.2.5 Sample volume investigation
[0227] The 20230323-01 batch of Morus alba bark furan slices were selected, and the samples were prepared according to method 7.2.4. The samples were injected with 0.05% phosphoric acid-acetonitrile mobile phase, and the peak of mulberry glycoside A was investigated when the injection volume was 5, 10, and 15 μL. The results are shown in Table 31. When the injection volume was 10 μL, the RSD value was 1.19%, which was smaller than the other two injection volumes, indicating that the injection was more accurate when the injection volume was 10 μL. Therefore, the injection volume was selected as 10 μL.
[0228] Table 31 Peak area of mulberry glycoside A in samples with different injection volumes
[0229]
[0230] 7.3 Determine system suitability conditions and solution preparation methods
[0231] 7.3.1 Chromatographic conditions and system suitability conditions
[0232] Octadecylsilane bonded silica gel is used as filler, 0.05% phosphoric acid water is used as mobile phase A, acetonitrile is used as mobile phase B, and gradient elution is performed according to the provisions of Table 20; the detection wavelength is 325 nm. The theoretical plate number calculated based on the mulberry glycoside A peak should be no less than 8000.
[0233] 7.3.2 Solution preparation method
[0234] Preparation of reference solution: Take an appropriate amount of mulberry glycoside A reference substance, weigh it accurately, and add 70% methanol to make a solution containing 0.5 g per 1 mL.
[0235] Preparation of test solution: Take about 0.5 g of the powder of the product (passed through a No. 4 sieve), accurately weigh it, place it in a stoppered conical flask, accurately add 25 mL of 70% methanol, weigh it, ultrasonically treat it (power 250 W, frequency 40 kHz) for 45 minutes, cool it, weigh it again, make up the lost weight with 70% methanol, shake it well, filter it, and remove the filtrate to obtain the solution.
[0236] Determination method: Accurately pipette 10 μL of reference solution and test solution respectively, inject into liquid chromatograph, and determine. Fig.25 and Table 32; the test results of mulberry glycoside A in Fuju decoction pieces are shown in Fig.26 and Table 32.
[0237] Table 32 Mulberry glycoside A HPLC system adaptability parameters
[0238]
[0239] 7.4 Study on the methodological determination of mulberry glycoside A content
[0240] 7.4.1 Investigation of linear relationships
[0241] Weigh 3.2 mg of Mulberiside A reference substance accurately, add 70% methanol to a 2 mL volumetric flask to obtain a 0.16 mg / mL standard solution, dilute 1.2, 2, 4, 10, 100, 250 times, and measure the peak area. Draw a standard curve with the injection volume of Mulberiside A as the horizontal axis X and the peak area as the vertical axis Y. The results are shown in Fig. 27 and Table 33. The regression equation is: y = 0.000000041610464x + 0.001415645964477, R 2 =0.9995. The results showed that mulberry glycoside A had a good linear relationship in the range of 0.0064 mg / mL-1.3 mg / mL.
[0242] Table 33 Results of investigation on linear relationship of different concentrations of Mulberry glycoside A
[0243]
[0244]
[0245] 7.4.2 Limit of detection and limit of quantification
[0246] Detection limit: The detection limit was determined according to the guidance for validation of analytical methods in the fourth general rules of the quality standards of the 2020 edition of the Chinese Pharmacopoeia. The signal measured by the known concentration of the test sample was compared with the signal measured by the blank sample, and the signal-to-noise ratio was 3:1. Fig.28 and Table 34. The lowest amount of mulberry glycoside A measured in the experiment was 0.0032 μg.
[0247] Table 34 Mulberry glycoside A detection limit system suitability parameters
[0248]
[0249] Limit of quantitation: The limit of quantitation was determined in accordance with the guidelines for validation of analytical methods in the fourth general rules of the 2020 edition of the Chinese Pharmacopoeia. The signal measured by the known concentration of the test sample was compared with the signal measured by the blank sample, and the signal-to-noise ratio was 10:1. Fig.29 and Table 35. The lowest amount of mulberry glycoside A measured in the experiment was 0.016 μg.
[0250] Table 35 System suitability for quantification limit of Mulberry glycoside A
[0251]
[0252] 7.4.3 Precision test
[0253] Take the same sample solution, inject it 6 times continuously according to the above conditions, determine the peak area of mulberry glycoside A, and calculate the RSD value of the peak area of mulberry glycoside A. The results are shown in Table 36. It can be seen that the RSD value of the peak area of mulberry glycoside A shows that the instrument precision is good.
[0254] Table 36 Precision test results
[0255]
[0256] 7.4.4 Repeatability test
[0257] Take 6 portions of the test solution, inject 6 times continuously according to the above conditions, determine the peak area of mulberry glycoside A, and calculate the peak area RSD value of mulberry glycoside A. The results are shown in Table 37. It can be seen that the average value of mulberry glycoside A content is 1.3%, and the RSD is 0.84%, indicating that the treatment method has good repeatability.
[0258] Table 37 Repeatability results of mulberry glycoside A in mulberry bark samples
[0259]
[0260] 7.4.5 Stability test
[0261] Weigh 0.5g of the sample powder of Morus alba bark furan decoction piece accurately, and accurately transfer 25mL of 70% methanol solution. After weighing, ultrasonicate for 45min, take it out and let it stand and cool, make up for the weight loss, take the supernatant through a 0.22μm microporous filter membrane and analyze the liquid phase to obtain the test solution. Samples are injected at 0, 2, 4, 6, 8, 10, 12, 18, 24, 36, and 48h after preparation, record the peak area of mulberry glycoside A and calculate the RSD value. The results are shown in Table 38. It can be seen from the RSD value of the peak area of mulberry glycoside A that mulberry glycoside A in the sample solution is stable within 48h, indicating that mulberry glycoside A has good stability.
[0262] Table 38 Results of stability test of mulberry glycoside A in mulberry bark samples
[0263]
[0264] 7.4.6 Content determination sample recovery test
[0265] Weigh 0.25g of the powder of the sample of Morus alba bark furan slices, accurately weigh it, place it in a 50mL conical flask, add 3.46mg of mulberry glycoside A reference substance at a ratio of 100%, accurately transfer 25mL of 70% methanol solution, weigh it, ultrasonicate it for 45min, take it out and let it stand to cool, make up for the weight loss, take the supernatant through a 0.22μm microporous filter membrane for liquid phase analysis, the injection volume is 10μL, determine the content of mulberry glycoside A, and calculate the sample recovery rate. The results are shown in Table 39. It can be seen that the sample recovery rate of mulberry glycoside A meets the sample recovery requirements under the corresponding content of the 2020 edition of the "Chinese Pharmacopoeia".
[0266] Table 39 Sample recovery test results
[0267]
[0268] 7.4.5 The content of mulberry glycoside A in 15 batches of Morus alba bark decoction pieces was determined. The specific test results are shown in Table 40.
[0269] Table 4015 Batch of Morus alba Fuju Decoction Pieces Content
[0270]
[0271]
[0272] It can be seen that the content of mulberry glycoside A in 15 batches of Morus alba slices is 1.39%-5.39%, with an average of 3.11%. The RAD of the test results of mulberry glycoside A at different sampling points in the same batch is 2.07%-5.80%, with an average of 3.82%; the content of mulberry glycoside A in 15 batches of Morus alba slices with pharmacopoeia specifications is 1.04%-6.32%, with an average of 3.40%. The RAD of the test results of mulberry glycoside A at different sampling points in the same batch is 0.29%-6.25%, with an average of 3.85%. The RAD of the 15 batches of Morus alba slices tested at different sampling points in the same batch is lower than that of the pharmacopoeia specifications, indicating that the quality of Morus alba slices is more uniform than that of the pharmacopoeia specifications. The 2020 edition of the Chinese Pharmacopoeia does not specify the content under the Morus alba slices. According to the experimental determination results of the content of 15 batches of Morus alba bark decoction pieces, 70% of the average value of 3.11% is 2.18%, so it is temporarily stipulated that the content of this product shall not be less than 2.0%.
[0273] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing Morus alba bark decoction pieces, characterized in that: The preparation method is: The mulberry bark medicinal material is steamed for 20-30 minutes, cut into small pieces of 4-6 mm in size, and dried to obtain the mulberry bark decoction pieces.
2. The preparation method according to claim 1, characterized in that: The moistening method is as follows: covering the mulberry bark medicinal material with two layers of wet gauze and spraying water once every 10 minutes.
3. The preparation method according to claim 1, characterized in that: The drying temperature is 60-70°C.
4. The Morus alba bark decoction pieces prepared by the preparation method according to any one of claims 1 to 3.
5. A method for preparing a standard decoction of Morus alba bark slices, characterized in that: After soaking the Morus alba bark decoction pieces as claimed in claim 4 in water, the pieces are decocted for the first time and for the second time, and the two decoctions are combined to obtain the standard decoction of the Morus alba bark decoction pieces.
6. The preparation method according to claim 5, characterized in that: During the soaking, the mass ratio of the Morus alba bark decoction pieces to the water is 1:10-12; and the soaking time is 20-40 minutes.
7. The preparation method according to claim 5, characterized in that: The first decoction time is 15-30 minutes, and the second decoction time is 15-30 minutes.
8. The quality control method of Morus alba bark decoction pieces according to claim 4, characterized in that: include: (1) performing powder microscopic identification on the Morus alba bark decoction pieces; (2) Testing the moisture content, total ash content and extract of the Morus alba bark decoction pieces; the moisture content of the Morus alba bark decoction pieces shall not exceed 10.0%, the total ash content shall not exceed 7.5%, and the extract shall not be less than 16.0%; (3) performing thin layer chromatography identification on the Morus alba bark decoction pieces; (4) The content of mulberry glycoside A in the Morus alba bark decoction pieces is detected by high performance liquid chromatography; the content of mulberry glycoside A shall not be less than 2.0%.
9. The quality control method according to claim 8, characterized in that: The thin layer chromatography identification method is as follows: 3 μL of the test solution and the reference solution are taken and spotted on a silica gel G thin layer plate, and a volume ratio of 1:6:2.5:0.1 of dichloromethane:ethyl acetate:methanol:acetic acid is used as a developing solvent, and after pre-saturation for 20 minutes, the plate is developed, taken out, dried, and observed under a 365 nm ultraviolet lamp; The preparation method of the test solution is as follows: the sample powder to be tested is mixed with ethanol in a ratio of 1 g: 30 mL, ultrasonically treated for 30 min under the conditions of 40 kHz and 250 W, filtered, and the filtrate is dried to obtain the test powder; the test powder is dissolved in ethanol in a ratio of 1 g: 5 mL to obtain the test solution; The preparation method of the reference substance solution is as follows: taking the mulberry glycoside A reference substance, adding methanol to prepare a solution containing 0.3 mg per 1 mL, and obtaining the reference substance solution.
10. The quality control method according to claim 8, characterized in that: The method of high performance liquid chromatography detection is: 10 μL of reference solution and test solution are taken, injected into liquid chromatograph, and chromatographed; The chromatographic conditions are as follows: octadecylsilane bonded silica gel as filler, 0.05% phosphoric acid water as mobile phase A, acetonitrile as mobile phase B, gradient elution as shown in the table below; detection wavelength: 325 nm; column temperature: 35° C.; flow rate: 1.0 mL / min; injection volume: 10 μL; The preparation method of the test solution is as follows: 0.5 g of the sample powder to be tested after passing through a No. 4 sieve is taken, 25 mL of 70% methanol is precisely added, ultrasonic treatment is performed for 45 min under the conditions of 40 kHz and 250 W, after constant volume, the sample is shaken, filtered, and constant volume is obtained to obtain the test solution; The preparation method of the reference substance solution is as follows: taking the mulberry glycoside A reference substance and adding 70% methanol to prepare a solution containing 0.5 g per 1 mL, thereby obtaining the reference substance solution.